The Future of War : the Re-Enchantment of War in the Twenty-First Century - Coker, Christopher (Rawalpindi GHQ)
Coker offers a new & provocative thesis about the future of war, arguing that biotechnology has provided the institution with a new lease of life.
Include Index
Keywords: War